KEPEMIMPINAN KEPALA SEKOLAH DALAM MENANGGAPI PEMBELAJARAN DI MASA PANDEMI COVID-19 - Hastuti, Meidina; Giatman, Muhammad; Ernawati, Ernawati (STKIP Pesisir Selatan, 2022)
The purpose of this research is to find out and explore the principal's management State Vocational High School 6 Padang on learning during the Covid-19 pandemic. This research was conducted using qualitative research methods, with the determination of selected participants (purposive sampling). Data collection is done through interviews, and field observation. We conducted data analysis using qualitative analysis methods. Results research shows that the leadership role of SMK Negeri 6 Padang in ensuring education is carried out through 3 main things, namely LMS development, LMS use training, and online teacher performance assessment. All of these leadership practices are forms of adaptive leadership that adapts to the conditions of the distance learning process that must be carried out during the Covid-19 pandemic.